Characterization of Athletic and Coach Liability arising from doping in Sport Halls (Bodybuilding as case study) - Shareef Ahmed , Shna; Hamad Smael , Dr.Tahsin (Basra studies journal, 2022)
The issue of the abuse of prohibited steroids is one of the most sensitive topics in the current era. Especially in the field of (sports bodybuilding). This sort of abuse is very common, whether it happens during the training phase in fitness halls or when participating in various competitions and Olympic Games due to the fact that they depend on the use of Sports steroids to increase the efficiency of athletes and win competitions. These drugs are frequently used by athletes illegally away from the medical field on different occasions without consulting specialists. The frequent usage goes back to the reason that in Iraq there is no special law that opposes and struggles against the use of steroids, which has greatly harmed athletes. This study discusses the nature of the civil liability of the coach and the athlete when using dangerous sports drugs illegally and outside the scope of medical care. They belong to contractual liability that together represent a contractual group. The coach’s liability is tortuous as an exception in other cases. This study also discusses cases in which the athlete himself is responsible for the damage due to the use of prohibited sports stimulants, and this is what causes the coach’s responsibility to be reduced from participating in the harm events and in the case of joint negligence and acceptance of sports risks.